The educational and careeriInterest scale (Science-Tecnology-Matematics): Validity and reliability study - Arslan, Serhat; Kurbanoğlu, Namudar İzzet (Journal of Human Sciences, 2015)
The aim of this study is to examine the psychometric features of Educational and Career Interest Scale (ECIS) developed by Oh et al. (2013) in order to assess the high school student's own interests in the fields of Science, Technology, and Mathematics (STEM) on Turkish sample. The scale consists of three sub dimensions called Science career interest (SCI), Technology career interest (TCI) and Mathematics career interest (MCI) as well as 9 items. The sample of the study comprises of 588 students who study at three different high schools. The studies of internal consistency, item and factor analysis and criterion cohesion validity were performed to examine the psychometric features of the scale. The values obtained from the internal consistency analyses of the scale was .89 for SCI sub dimension; .81 for TCI sub dimension; .88 for MCI sub dimension and .87 in total, and it was shown that the scale has sufficient reliability levels. The results of item discrimination and confirmatory factor analysis showed that the original three-factor structure of the scale is suitable for Turkish sample. So, it is thought that the scale is a valid and reliable tool to be used for determining the educational and career interest levels for Turkish sample group.